Dinuclear Organotin Building Blocks and their Conversion into a Tetranuclear Macrocycle Containing Sn−O−Sn Linkages. Issue 22 (26th May 2021) - Gómez‐Jaimes, Gelen; Rojas León, Irán; Martínez Romero, Rodolfo; Beltrán, Hiram I.; Rodríguez‐Molina, Braulio; Hiller, Wolf; Jurkschat, Klaus; Hernández, Irán F.; Höpfl, Herbert
Abstract: Six dinuclear organotin building blocks of general composition RR′R′′SnCH2 Si(CH3 )2 −biphenyl−Si(CH3 )2 CH2 SnR′′R′R, in which the tin atoms are separated by a p, p ′‐biphenylene bridge and carry different substituents [BD1 with R, R′=CH2 Si(CH3 )3, R′′=Ph; BD2 with R, R′=CH2 Si(CH3 )3, R′′=Cl; BD3, with R, R′=CH2 Si(CH3 )3, R′′=I; BD4 with R=CH2 Si(CH3 )2 (C5 H4 FeCp), R′, R′′=Ph; BD5 with R=CH2 Si(CH3 )2 (C5 H4 FeCp), R′=Ph, R"=Cl; BD6 with R=CH2 Si(CH3 )2 (C5 H4 FeCp ), R′=Ph, R′′=I], were synthesized and characterized by spectroscopic and spectrometric methods. Furthermore, the crystal and molecular structures of BD2 were determined by single‐crystal X‐ray diffraction (SCXRD) analysis, revealing the formation of molecular strands through intermolecular Cl→Sn contacts. The 1D coordination polymer [BD2 ]n comprises macrocyclic rings of composition [BD2 ]2 that motivated the generation of a related molecular macrocyclic structure by reaction of BD2 with silver (I) oxide in a 2 : 2 stoichiometry. The [2+2] macrocyclization yielded the 30‐membered tetra‐nuclear ring structure M1, viz ., {[R2 SnCH2 Si(CH3 )2 −biphenyl−(CH3 )2 SiCH2 SnR2 ]( μ‐ O)}2, in which two BD2 dinuclear building blocks are linked through two covalent Sn−O−Sn moieties. Examination by DFT calculations at the B3LYP/def2svp and B3LYP/6‐31G*(C, H, O, Si)/LanL2DZ(Sn) levels of theory gave energy minima for molecular conformers of M1 carrying the Sn−O−Sn and p, p ′‐biphenylene bridges in syn ‐ or anti ‐orientation. Abstract : Dinuclear organotin halides carrying CH2 SiMe3 and ferrocenyl‐substituents were prepared and found suitable for the synthesis of a tetra‐nuclear 30‐membered macrocycle via fusion through Sn−O−Sn bridges.